2021
DOI: 10.3390/ma14061383
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible and Repeatable Shape Transformation of Additively Manufactured Annular Composite Structures

Abstract: Four-dimensional (4D) printing is a unique application of additive manufacturing (AM) which enables additional shape transformations over time. Although 4D printing is an interesting and attractive phenomenon, it still faces several challenges before it can be used for practical applications: (i) the manufacturing cost should be competitive, and (ii) the shape transformations must have high dimensional accuracy and repeatability. In this study, an irreversible and repeatable thermoresponsive shape transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…It is vital for 4DP of SMP-based products to undergo a transition between two pre-defined shapes. [68,110,111] In other words, the programming of polymeric materials helps in setting secondary configurations. In this technique, the materials are heated above their glass transition temperature (T g ) and strains are induced.…”
Section: Programming Of Smmsmentioning
confidence: 99%
“…It is vital for 4DP of SMP-based products to undergo a transition between two pre-defined shapes. [68,110,111] In other words, the programming of polymeric materials helps in setting secondary configurations. In this technique, the materials are heated above their glass transition temperature (T g ) and strains are induced.…”
Section: Programming Of Smmsmentioning
confidence: 99%
“…A vast range of SMP matrices have been investigated including polyl(actic acid) (PLA), polyimide, poly(ε-caprolactone) (PCL), ethylene-vinyl acetate (EVA), and acrylonitrile butadiene styrene (ABS). 14 Research on polymer blend systems have also shown excellent results, which often produce enhanced mechanical and shape memory performance through the intentional selection of the two differing polymer matrices. For example, Lai et al fabricated PLA/TPU bio-based polymer blends and reported that the addition of TPU improved the recovery ratio of PLA by 93.5 ± 0.4% when predeformed at 25 °C and activated at 160 °C (50:50 TPU/PLA).…”
Section: Introductionmentioning
confidence: 99%
“…A vast range of SMP matrices have been investigated including polyl­(actic acid) (PLA), polyimide, poly­(ε-caprolactone) (PCL), ethylene-vinyl acetate (EVA), and acrylonitrile butadiene styrene (ABS) . Research on polymer blend systems have also shown excellent results, which often produce enhanced mechanical and shape memory performance through the intentional selection of the two differing polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting extruded strands undergo residual stress: tensile residual stress along the printing direction and compressive residual stress along the lateral direction. The printing paths have been programmed to induce anisotropy along unidirectional (Bodaghi et al, 2017;Hu et al, 2017;Rajkumar and Shanmugam, 2018;Bodaghi et al, 2019;Goo et al, 2021) or bidirectional (Van Manen et al, 2017;Goo et al, 2020) laminations. Accordingly, a part printed via a specially programmed printing path deforms when an appropriate thermal stimulus is applied to release the residual stress, which results in one-way irreversible shape transformation unlike the conventional 4D printing methods that use smart materials.…”
Section: Introductionmentioning
confidence: 99%
“…As a thermal stimulus, convective heating has generally been used by immersing an anisotropically printed sample in hot water (Bodaghi et al, 2017;Hu et al, 2017;Bodaghi et al, 2019). For an acrylonitrile butadiene styrene (ABS) sample, on the other hand, an electric oven was used for the convective heating (Goo et al, 2020;Goo et al, 2021) because its glass transition temperature is higher than 100 °C. Although these convective heating methods provide uniform heating capability, their thermal responses are relatively slow due to the low convection coefficient of air.…”
Section: Introductionmentioning
confidence: 99%